Apakah Perbedaan Gaya Kepemimpinan dan Skema Kompensasi Mempengaruhi Negosiasi Harga Transfer? - Aryan Danil Mirza. BR; Fitri Mareta (Journal of Applied Accounting and Taxation, 2022)
Transfer pricing can cause conflicts between divisions. Therefore, this study examines how the type of leadership and compensation schemes can influence the seller's transfer price decision to obtain an equal profit—using a 2x2 factorial design experimental method on leadership Style variables (supportive vs. unsupportive) and compensation scheme variables (high bonus percentage vs. low bonus percentage). This study shows that sellers will charge transfer prices close to the same profit under supportive leadership. In addition, the seller will charge a transfer price close to the same profit when the compensation scheme has a low bonus percentage. This study provides knowledge to companies to formulate effective strategies to reduce transfer price negotiation conflicts by considering the type of leadership and compensation schemes.